2013
DOI: 10.1556/oh.2013.29744
|View full text |Cite
|
Sign up to set email alerts
|

Attendance of the fourth (2008–2009) screening round of the Hungarian organized, nationwide breast cancer screening program

Abstract: In order to decrease the mortality due to breast cancer, the attendance rate of mammography screening programme should be increased. Orv. Hetil., 154(50), 1975-1983.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
2
0
2
Order By: Relevance
“…Several reasons can be attributed to this phenomenon. First, although breast cancer screening programs have been implemented for almost 20 years in Hungary, participation rates were still below 50% in the 2000s, which seems significantly lower than the ideal 70% required to achieve a significant impact on breast cancer mortality (43)(44)(45). In addition, a recent Hungarian cross-sectional study revealed significant knowledge gaps in the field of breast cancer screening recommendations among women.…”
Section: Discussionmentioning
confidence: 99%
“…Several reasons can be attributed to this phenomenon. First, although breast cancer screening programs have been implemented for almost 20 years in Hungary, participation rates were still below 50% in the 2000s, which seems significantly lower than the ideal 70% required to achieve a significant impact on breast cancer mortality (43)(44)(45). In addition, a recent Hungarian cross-sectional study revealed significant knowledge gaps in the field of breast cancer screening recommendations among women.…”
Section: Discussionmentioning
confidence: 99%
“…A szervezett népegészségügyi szűrési programokon való részvételi arányokat és a teljes lefedettség alakulását a két daganatféleség esetén korábban részletesen elemezték. Az emlőszűrés esetén az első 2002-2003-as szűrési ciklusban a részvételi arány 45,1%, a 2004-2005-ös ciklusban 37,2%, míg a következő két szűrési ciklusban 41% és 42,7% volt, ami elmaradt a WHO 70%-os célkitűzésétől [15][16][17][18]. A 45-65 éves női célpopulációban a szűrési (átszűrtség) és diagnosztikus (átvizsgáltság) emlőfelvétellel rendelkezők aránya (teljes lefedettség) az első szűrési ciklusban 53,5%-os, míg a következő ciklusokban 50,8%, 49,7% és 51,0% volt, tehát a 2002-2009-es időszakban érdemi változás nem történt [15][16][17][18].…”
Section: Eredeti Közleményunclassified
“…The country has a long history of population-level breast cancer screening, having established the national programme in 2002 for women aged 45-65 years with a two-year screening interval [1] . Before the pandemic, the examination rate in the target population was between 45-60% depending on the age group [2] .…”
Section: Introductionmentioning
confidence: 99%